In the grip of necrocapitalism : the making and breaking of a psychonomy / George Tsakraklides. - Tsakraklides, George (publisher not identified, 2023)
This volume looks into the human condition through a wide frame of reference which covers not only our accomplishments, but also the tragic failures which have led to the global collapse of industrial civilisation currently taking place. While traditional history and anthropology tend to focus on how we got from point A to point Z, this book will be focusing on how we got from A to Zero, via Z. Because it is precisely our accomplishments which have been our downfall, therefore raising the need for a fresh post-mortem account of events that can attempt to integrate accomplishments and downfalls as part of one, cohesive story which resonates whichever way one may choose to read it: front to back, or back to front. This is the story of how we became victims of, and slaves to, our own ambitions.